Pengembangan Kemampuan Berpikir Analitis Peserta Didik Melalui Model Pembelajaran Prepare, Do, Review pada Materi Indikator Asam Basa - Bestiana Desti; Tritiyatma Hadinugrahaningsih; Yusmaniar Yusmaniar (LPPM Universitas Negeri Jakarta, 2020)
This study aimed to develop students' analytical thinking skills through the Prepare, Do, Review learning model on acid and base indicator topics. The study was conducted at SMAN 36 Jakarta in the 2018/2019 academic year with the subjects 33 students of class XI MIPA 4. The study employed qualitative methods by collecting data through tests, observation, and reflective journals. The Prepare, Do, Review model implemented through three stages of learning, namely preparation, conducting activities, and review. Analytical thinking ability include of three indicators, namely diffrerentiating, connecting, and organizing. Indicators of analytical thinking ability to be achieved are adjusted to the indicators of achievement of existing competencies. The overall results of the study showed 84,85% of students reached very good levels, 15,15% reached good levels, and there were no more students who were at a fair level, poor level and not very poor level. In each indicator of analytical thinking ability on acid and base indicator topics, there are no students at poor level and very poor level which suggests that learners’ analytical thinking skills develop. Prepare, Do, Review creates a meaningful learning process because learners have experience in learning process, so this model can develop the ability of learners’ analytical thinking. Keywords Prepare Do Review, analytical thinking ability, acid base indicator